2018
DOI: 10.3389/fcimb.2018.00249
|View full text |Cite
|
Sign up to set email alerts
|

Incompatible Translation Drives a Convergent Evolution and Viral Attenuation During the Development of Live Attenuated Vaccine

Abstract: Live attenuated vaccines are widely used to protect humans or animals from pathogen infections. We have previously developed a chicken embryo-attenuated Duck Hepatitis A Virus genotype 1 (DHAV-1) vaccine (CH60 strain). This study aims to understand the mechanisms that drive a virulent strain to an attenuated virus. Here, we systematically compared five DHAV-1 chicken embryo attenuated strains and 68 virulent strains. Phylogenetic analysis indicated that duck virulent strains isolated from different geographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
(79 reference statements)
0
9
0
2
Order By: Relevance
“…Além disso, AGCC ligam-se à receptores Gpr43 expressos em diversos tecidos, incluindo o cólon, estimulando a secreção de glucagon-like peptide 1 (GLP-1), um hormônio anorexígeno que melhora a sensibilidade à insulina e através da supressão desta, previne o acúmulo de tecido adiposo. (1) Os AGCC podem também interagir com o receptor Gpr41, situado nas células enteroendócrinas, liberando o hormônio PYY, que apresenta a capacidade de diminuir a extração de energia dos componentes alimentares, além de reduzir a motilidade intestinal, reduzindo, consequentemente, o trânsito intestinal. (24) Ainda que o ganho de peso tenha sido maior entre os animais que receberam apenas dieta de cafeteria, não foram apresentadas diferenças estatísticas quanto ao consumo total e diário de dieta entre os grupos experimentais.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Além disso, AGCC ligam-se à receptores Gpr43 expressos em diversos tecidos, incluindo o cólon, estimulando a secreção de glucagon-like peptide 1 (GLP-1), um hormônio anorexígeno que melhora a sensibilidade à insulina e através da supressão desta, previne o acúmulo de tecido adiposo. (1) Os AGCC podem também interagir com o receptor Gpr41, situado nas células enteroendócrinas, liberando o hormônio PYY, que apresenta a capacidade de diminuir a extração de energia dos componentes alimentares, além de reduzir a motilidade intestinal, reduzindo, consequentemente, o trânsito intestinal. (24) Ainda que o ganho de peso tenha sido maior entre os animais que receberam apenas dieta de cafeteria, não foram apresentadas diferenças estatísticas quanto ao consumo total e diário de dieta entre os grupos experimentais.…”
Section: Discussionunclassified
“…Acredita-se que a microbiota intestinal esteja relacionada com anormalidades cardiometabólicas e hábitos alimentares. (1) Além da dieta, fatores fisiológicos e ambientais, como estilo de vida e utilização de antibióticos, tornam o ambiente intestinal particular entre os indivíduos. (2) O conteúdo excessivo de gordura na alimentação contribui para diversas doenças como obesidade, diabetes e doenças cardiovasculares.…”
Section: Introductionunclassified
“…A codon is degenerate in nature, that is, there are multiple codons coding for the same amino acid. In an organism, the genome has degenerate codons; however, it has been observed that among synonymous codons, there are certain codons that are expressed more; thus, a codon bias may exist in certain species (36,37). For example, in the case of poliovirus, a change in the genome sequence of type-2 strain by increasing the frequency of CpG and UpA dinucleotides results in the decrease of codon bias, followed by the attenuation of the virus due to the lowered expression of toxins and lowered replication rate, which were found to be conserved after several passages in HeLa cells (36,38,39).…”
Section: Attenuation By Codon Targetingmentioning
confidence: 99%
“…However, for viruses of the order Nidovirales, both the synthesis of positive-stranded genomic RNAs and the transcription of subgenomic mRNA (sg mRNA) are required for viral replication. The sg mRNA contains same 5 ′ and 3 ′ -termini and will be translated to produce different structural proteins (Pasternak et al, 2006;Cao et al, 2012Cao et al, , 2013Cao et al, , 2016Sun et al, 2016Sun et al, , 2017Ou et al, 2017Ou et al, , 2018Lai et al, 2019;Wen et al, 2019). Suthar et al (2013)].…”
Section: Introductionmentioning
confidence: 99%